Rehabilitative treatment of patients with COVID-19 infection: the P.A.R.M.A. evidence based clinical practice protocol: Covid-19 P.A.R.M.A. Protocol - Petraglia, Federica; Chiavilli, Marco; Zaccaria, Barbara; Nora, Monica; Mammi, Patrizia; Ranza, Elena; Rampello, Anais; Marcato, Antonio; Pessina, Fabio; Salghetti, Annamaria; Costantino, Cosimo; Frizziero, Antonio; et al. (Acta Biomedica Atenei Parmensis, 2020)
Background: The impact of the SARS-CoV-2 on the National Health System (NHS) required a reorganization of the various levels of care, which also involved the rehabilitation reality. Aim of the work: A clinical practice review of the literature was conducted to provide operational-rehabilitation guidelines adapted to the local reality and to the recent corporate reorganization in the context of the COVID-19 emergency. Methods: A practice review of the available scientific evidence was regularly conducted from the start of the COVID-19 pandemic to periodically update the clinical practice guidelines. Articles that met the following inclusion criteria were included: studies conducted on human adult subjects with COVID-19 infection, undergoing rehabilitation in any hospitalization setting. Results: The results of this clinical practice update were periodically discussed with colleagues and collaborators in a multi-professional team, in order to guarantee a good clinical practice protocol, named P.A.R.M.A. Conclusions: The P.A.R.M.A. protocol is the result of a periodic review literature update, which has allowed us to take charge of patients affected by COVID-19 according to the most up-to-date clinical evidences, guaranteeing a shared and uniform treatment within a local reality in an era of health emergency.